Analisis Terhadap Sebutan Nama Tuhan Keadilan Kita di Yeremia 33:16 dan Aplikasinya dalam Kehidupan - Waruwu, Kharisda Mueleni; Widodo, Priyantoro (Pusat Studi Pentakosta Indonesia, 2022)
Understanding of the designation for God among Christians, of course, some know and also have understood it and even become a familiar name. The designation for the name of God or the title given to that name, always has a different background according to what the people experienced at that time. For example